2007
DOI: 10.1111/j.1600-0854.2007.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Kinesin‐Binding Domain of RanBP2 to KIF5B and KIF5C Determines Mitochondria Localization and Function

Abstract: The Ran-binding protein 2 (RanBP2) is a large mosaic protein with a pleiotropic role in cell function. Although the contribution of each partner and domain of RanBP2 to its biological functions are not understood, physiological deficits of RanBP2 downregulate glucose catabolism and energy homeostasis and lead to delocalization of mitochondria components in photosensory neurons. The kinesin-binding domain (KBD) of RanBP2 associates selectively in the central nervous system (CNS), and directly, with the ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 44 publications
1
109
0
4
Order By: Relevance
“…Therefore, our data establish the tail HM site as a regulatory focal point. The RanBP2 protein is also likely to be another extrinsic direct regulator of the HM site (47).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our data establish the tail HM site as a regulatory focal point. The RanBP2 protein is also likely to be another extrinsic direct regulator of the HM site (47).…”
Section: Resultsmentioning
confidence: 99%
“…We next examined potential cross-reactivities among kinesin-1 antibodies. The production of bacterially expressed full-length recombinant kinesin-1 polypeptides in bacteria mainly resulted in the formation of truncated species of lower molecular mass (37), thus complicating the identification of properly folded, full-length kinesin-1 polypeptides that would enable appropriate antibody characterization. To circumvent these issues, anti-kinesin-1 antibodies were reacted with lysates derived from COS-7 cells transfected with cDNAs coding for 6-His-tagged, full-length mouse kinesin-1A, kinesin-1B, or kinesin-1C ( Figure 1C).…”
Section: Characterization Of Anti-kinesin-1 Antibodiesmentioning
confidence: 99%
“…It was suggested that the kinesin plus end directed motor could pay a role in delivering cargo to, or taking it away from, the NPC (Mavlyutov et al 2002), a function that may be more crucial in cells with long distance transport requirements, such as neurons. However, it was shown that the kinesin-Nup358 interactions are related to functions away from the NPC in determining the correct localisation and function of mitochondria (Cho et al, 2007). Interestingly, the kinesin binding domain, together with the two flanking ran binding domains, activate the kinesin motor activity of KIF5C (Cho et al, 2009), suggesting that any kinesin bound to Nup358, whether it is in the cytoplasm or at the NPC, would be an active motor.…”
Section: Nup358 Binds To Kinesinsmentioning
confidence: 99%